Asymmetric Thermally Activated Delayed Fluorescence Materials With Aggregation-Induced Emission for High-Efficiency Organic Light-Emitting Diodes - Li, Huanhuan; Zhi, Yibin; Dai, Yizhong; Jiang, Yunbo; Yang, Qingqing; Li, Mingguang; Li, Ping; Tao, Ye; Li, Hui; Huang, Wei; Chen, Runfeng (Frontiers in Chemistry, 2020)
The exploitation of thermally activated delayed fluorescence (TADF) emitters with aggregation-induced emission is highly prerequisite for the construction of highly efficient electroluminescent devices in materials science. Herein, two asymmetric TADF emitters of SFCOCz and SFCODPAC with charming aggregation-induced emission are expediently designed and prepared based on highly twisted strong electron-withdrawing acceptor (A) of sulfurafluorene (SF) modified ketone (CO) and arylamine donor (D) in D1-A-D2 architecture by simply synthetic procedure in high yields. High photoluminescence quantum yields up to 73%, small singlet-triplet splitting of 0.03 eV, short exciton lifetimes are obtained in the resultant molecules. Strikingly, efficient non-doped and doped TADF OLEDs (organic light-emitting diodes) facilitated by these emitters show high luminance of 5598 and 11595 cd m-2, CEs of 16.8 and 35.6 cd/A, PEs of 9.1 and 29.8 lm/W and EQEs of 7.5% and 15.9%, respectively. This work furnishes a concrete instance in exploring efficient TADF emitter, which is highly conducive and encouraging in stimulating the development of TADF OLEDs with high brightness and excellent efficiencies simultaneously.